GUA-GUA HUNIAN PRASEJARAH DI PULAU ROTE, INDONESIA TIMUR - jatmiko (Berkala Arkeologi, 2010)
This article is written based on the results of several archaeological investigations carried out by the National Research and Development Centre of Archaeology in prehistoric caves, in the Rotendao Regency on the Island of Rote, the Province of East Nusa Tenggara between 2006 - 2009. The investigations were focused on Mbia Hudale, Bafak, and Bote caves which are assumed to have prolific archaeological remains. Excavations on these caves reveal traces of human occupation dated back to Late Pleistocene - Holocene epoch. This is evident in the abundance of cultural remains found in these sites, such as plain and decorated potteries, mollusk shells, jewelry (beads) made of shell, lithic stone flakes and blades, as well as faunal remains. Not a single human bone was found during the excavations. Furthermore, archaeological surveys conducted in this area have identified 18 potential caves and rockshelters, as well as a Palaeolithic opensite which are scattered within 8 districts. The results of the researches suggest that prehistoric caves in the Island of Rote are potential and prospective in illuminating prehistoric human migration and cultural processes that took place in the eastern part of Indonesia during Late Pleistocene until Holocene epoch.